2019
DOI: 10.1002/aic.16682
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of segregation and fluidization of binary mixtures in a cylindrical fluidized bed

Abstract: Dynamics of segregation and fluidization of unary particles and binary mixtures in a cylindrical fluidized bed is investigated using temporally– and spatially–resolved measurements of solids volume fraction (αs) performed using Electrical Capacitance Tomography (ECT). Through the comparison with high‐speed imaging, we have shown that ECT can be used to measure the segregation behavior in cylindrical fluidized beds quantitatively. ECT measurements have been used further to quantify the effects of mixture compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…The segregation percentage decreased as the sand particle size decreased, and the sisal residue particle size increased. This result is not in line with the work of Singh et al [29], which showed that the smallest particle size contributes to a well-mixed bed.…”
Section: Segregation Behaviorcontrasting
confidence: 99%
“…The segregation percentage decreased as the sand particle size decreased, and the sisal residue particle size increased. This result is not in line with the work of Singh et al [29], which showed that the smallest particle size contributes to a well-mixed bed.…”
Section: Segregation Behaviorcontrasting
confidence: 99%
“…A comparison of measured and predicted particle dispersion heights (bed expansion) for Geldart Group-B (G922) and Group-A (G96) particles is shown in Figure . A high-speed photographic imaging technique was used to measure the particle dispersion heights . The spread bars shown on the measured and predicted dispersion heights at different U G represent the maximum and minimum dispersion heights.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The instantaneous change in the α s distributions over the bed cross section was measured using ECT at an axial height of z = 24 cm from the distributor plate. From the measured α s distributions, the time evolution of α s distributions along the diameter of the bed was extracted and is shown in Figure a . A similar methodology was used to calculate the time evolution of α s distributions from the simulations data (Figure b–d).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations